Effect of Implantable Electrical Nerve Stimulation on Cortical Dynamics in Patients With Herpes Zoster–Related Pain: A Prospective Pilot Study - Zhou, Haocheng; Han, Rui; Chen, Li; Zhang, Zhen; Zhang, Xiaobo; Wang, Jianlong; Liu, Zuoliang; Huang, Dong (Frontiers in Bioengineering and Biotechnology, 2022)
Implantable electrical nerve stimulation (ENS) can be used to treat neuropathic pain caused by herpes zoster. However, less is known about the cortical mechanism induced by the neuromodulation therapy. Here, we recorded the 16-channel resting-state electroencephalogram after implantation of spinal cord stimulation (n=5) or peripheral nerve stimulation (n=3). Comparison of neuromodulatory effect was examined under distinct condition (ENS active versus. rest). To capture the cortical responses of ENS, spectral power and coherence analysis were performed. ENS therapy achieved satisfactory relief from pain with mean VAS reduction of 5.9 ± 1.1. Spectral analysis indicated that the theta and alpha oscillations increased significantly during the activation of neuromodulation, compared with the resting state. Furthermore, ENS administration significantly increased the frontal-frontal coherence in the alpha band. Our finding demonstrated that, despite methodological difference, both spinal cord and peripheral nerve stimulation induced cortical changes of alpha oscillations in patients with zoster-related pain. The dynamic change, in part, may mediate the analgesic effect of ENS on herpes zoster-related pain.